2004
DOI: 10.1128/jvi.78.19.10258-10264.2004
|View full text |Cite
|
Sign up to set email alerts
|

Defining T-Cell-Mediated Immune Responses in Rotavirus-Infected Juvenile Rhesus Macaques

Abstract: The appearance of virus-specific CD4؉ and/or CD8 ؉ T lymphocytes in peripheral blood of captive juvenile rhesus macaques (Macaca mulatta) was observed following rotavirus infection. These cell-mediated immune responses were measured following experimental or natural infection after rotavirus was isolated from stool specimens of asymptomatic animals. The virus isolated was a new strain of simian rotavirus that we named TUCH (for Tulane University and Cincinnati Children's Hospital). Restimulation of peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
(53 reference statements)
3
28
0
Order By: Relevance
“…Recent studies of T cell responses in human PBL showed that in rotavirus infected children, virus-specific CD4+ and CD8+ T cells that secreted IFN-γ were very low or undetectable [19,49]. Similar results were found in studies of rotavirus-infected juvenile rhesus macaques monkeys [50]. Studies of intestinal and systemic rotavirus-specific ASC and lymphocyte proliferation responses in Gn pigs at various time points indicated that blood mirrored the IgA ASC and lymphocyte proliferation responses in the gut, but at a lower level, and could serve as a temporary "window" for monitoring intestinal immune responses to rotavirus.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent studies of T cell responses in human PBL showed that in rotavirus infected children, virus-specific CD4+ and CD8+ T cells that secreted IFN-γ were very low or undetectable [19,49]. Similar results were found in studies of rotavirus-infected juvenile rhesus macaques monkeys [50]. Studies of intestinal and systemic rotavirus-specific ASC and lymphocyte proliferation responses in Gn pigs at various time points indicated that blood mirrored the IgA ASC and lymphocyte proliferation responses in the gut, but at a lower level, and could serve as a temporary "window" for monitoring intestinal immune responses to rotavirus.…”
Section: Discussionsupporting
confidence: 74%
“…The virus titers were determined using a cell culture immunofluorescence (CCIF) assay [3]. The 50% infectious dose (ID 50 ) and diarrhea dose (DD 50 ) of Wa VirHRV was determined previously in Gn pigs as ≤1 FFU [37]. The 37th cell culture passage of Wa AttHRV was propagated in the African green monkey kidney cell line MA104 and used for vaccination at a dose of 5×10 7 FFU and as stimulating antigen (HRV antigen) in intracellular cytokine staining of IFN-γ producing or proliferating T cells.…”
Section: Virusesmentioning
confidence: 99%
“…The ages of the macaques on their day of inoculation are specified in Table 6. Shedding data for macaques FB82, FB88, and FB97 were already provided in tabular form in a very recent publication (39).…”
Section: Discussionmentioning
confidence: 99%
“…7). The presence of IL-12 has been reported in the supernatants of cultures of simian DC treated with RV and T cells (52).…”
Section: Cd4mentioning
confidence: 99%
“…We have previously shown that human monocytes treated in vitro with RV are able to present antigen to specific CD4 ϩ T cells (48). Recently, it was also reported that DC treated with RV can stimulate RV-specific T cells from rhesus macaques (52). Our knowledge of the APC that probably present RV antigen in vivo comes from animal models: viral antigen has been detected in the Peyer's patches, mesenteric lymph nodes, and spleens of mice up to 20 days after RV infection (8).…”
mentioning
confidence: 99%